Short Communication: Sexual dimorphism of Hill Blue Flycatcher (Cyornis banyumas) in Hill Evergreen Forest, Mae Sa-Kog Ma Biosphere Reserve, Chiang Mai Province, Thailand - PAANWARIS PAANSRI; SUPALAK SIRI; YUWADEE PONPITHUK; WARONG SUKSAVATE; MONGKOL SAFOOWONG; WIMONMART NUIPAKDEE; PRATEEP DUENGKAE (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Paansri P, Siri S, Ponpithuk Y, Suksavate W, Safoowong M, Nuipakdee W, Duengkae P. 2019. Sexual dimorphism of Hill Blue Flycatcher (Cyornis banyumas) in Hill Evergreen Forest, Mae Sa-Kog Ma Biosphere Reserve, Chiang Mai Province, Thailand. Biodiversitas 20: 1544-1548. A sample consisting of 60 males and 39 females Cyornis banyumas captured in the Mae Sa-Kog Ma Biosphere Reserve was examined using 42 morphometric characters to assess sexual dimorphism. The results of the univariate analysis showed that there were ten morphometric traits (Ltail, TLF, C-middle, HB, C-outer, T-inner, C-digit, T-middle, DUTET and LG) that could be used for discrimination of sexual differences. The morphological data based on significant differences revealed that males were larger than females. The results of discriminant analysis based on the significant differences of nine raw morphometric data can be used to construct a sexual discrimination equation (D) where D = -22.051 + 0.368 (Ltail). The sexual discrimination equation can be directly used to identify both sexes with 79.6% of cross-validated grouped cases correctly classified, since positive D scores indicated males and negative D scores indicated females, with 81.4% of the males and 74.4% of the females being correctly assigned with a cutoff value between sexes = 0.